1989
DOI: 10.1128/mcb.9.8.3482-3490.1989
|View full text |Cite
|
Sign up to set email alerts
|

Germ Line c-myc Is Not Down-Regulated by Loss or Exclusion of Activating Factors in myc-Induced Macrophage Tumors

Abstract: As in tumors with c-myc chromosomal translocations, c-myc retrovirus-induced monocyte tumors constitutively express an activated form of c-myc (the proviral gene), whereas the normal endogenous c-myc genes are transcriptionally silent. Treatment of these retrovirus-induced tumor cells with a number of bioactive chemicals and growth factors that are known to induce c-myc expression in cells of the monocyte lineage failed to induce the endogenous c-myc gene. In contrast, the same treatments induced the c-fos gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

1991
1991
1992
1992

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 54 publications
0
0
1
Order By: Relevance
“…Interestingly, we have observed that the endogenous c-myc was not downregulated by the high level of c-myc transgene expression either in thymomas or in thymic cells from young animals. This finding contrasts with those of a number of studies in which such downregulation was observed in myc-induced tumors (2,3,17,24,28,29,33,39,40).…”
Section: Discussioncontrasting
confidence: 99%
“…Interestingly, we have observed that the endogenous c-myc was not downregulated by the high level of c-myc transgene expression either in thymomas or in thymic cells from young animals. This finding contrasts with those of a number of studies in which such downregulation was observed in myc-induced tumors (2,3,17,24,28,29,33,39,40).…”
Section: Discussioncontrasting
confidence: 99%